If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2x + -7) = 4 Reorder the terms: -1(-7 + 2x) = 4 (-7 * -1 + 2x * -1) = 4 (7 + -2x) = 4 Solving 7 + -2x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2x = 4 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 4 + -7 -2x = 4 + -7 Combine like terms: 4 + -7 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5
| ln(30)+ln(x)=24ln(x+1) | | x+4=4x-10 | | 1.5p=-0.3 | | 2.2+p=1 | | 2y+3=5 | | z^2-8iz-16=0 | | 7c-3c=2c+24 | | 96-4y=84 | | 4+7n=n/6 | | 9q=99 | | y/7=.25 | | s-20=33 | | 23*x=46 | | 3-20=33 | | (3x+7)/7=4 | | z^2-8z-5p=0 | | a=8.34fc | | 2(y-3)=-3 | | 7x-3x^2=85+2x^2+2x | | 5-4m=17 | | 5(w+2)=3(w+6) | | 16x^2-7x=17x-9 | | z^2-8iz-5p=0 | | 7x+y=-4 | | 5x^2+40x+100=25 | | 5(x-17)=2(x-3) | | 2X^3+6X^2-2x=0 | | A=s | | 3x^2+12x=131-2 | | 3x^5+12x=131-2 | | 23x+34=23-12x-7x | | b^2+9b+10=-8 |